Peran Guru dan Keluarga dalam Pembinaan Iman Siswa di Sekolah - Selfina Selfina (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
The development of faith among students is a critical component of holistic education aimed at shaping moral character and spiritual resilience. In the midst of rapid technological and social change, students are exposed to diverse influences that challenge their spiritual values. This study employs a literature review (library research) method, analyzing various sources including academic journals and relevant books published within the last five to ten years. The findings reveal that teachers play a central role as educators, role models, motivators, and guides in the faith development of students at school. Families, as the primary educational environment, contribute foundational faith formation through consistent example and habituation in daily life. Furthermore, collaborative relationships between teachers and families are essential for creating a supportive environment for students' spiritual growth. However, several challenges hinder this process, including low student motivation, negative peer influence, and lack of family engagement. It is recommended that schools and families develop more interactive, contextual, and sustained approaches to faith formation so that students may grow into individuals of strong faith, noble character, and social responsibility space.